Studi Karakteristik Hujan Tunggal di Kawasan Iklim Muson Tropik, Studi Kasus Sifat Hujan di Yogyakarta - Andreas S.W.; Sahid S.; Darmadi Darmadi (agriTECH, 1992)
A study on the characteristics of rainfall in tropical monsoon climate region was emphasized to analyze a single rainfall with frequency distribution modeling approach. The study was conducted at Yogyakarta. The results indicate that the 80% occurrence of rain fall in normal and upper normal conditions was less than 12 mm depth. The fit of the exponential and gamma distributions to the rainfall depth data were accepted. The starting hour or of rainfall was found after midday. especially for the amount rainfall more than 12 mm. The rainfall duration 12 - 16 mm depth occurred mainly less